Pharmacological Activities of Safflower Yellow and Its Clinical Applications. (27th June 2022) - Chen, Yan; Li, Meifeng; Wen, Jiayu; Pan, Xiaoqi; Deng, Zixin; Chen, Junren; Chen, Guanru; Yu, Lei; Tang, Yunli; Li, Gangmin; Xie, Xiaofang; Peng, Cheng
Abstract : Background . Safflower is an annual herb used in traditional Chinese herbal medicine. It consists of the dried flowers of the Compositae plant safflower. It is found in the central inland areas of Asia and is widely cultivated throughout the country. Its resistance to cold weather and droughts and its tolerance and adaptability to salts and alkalis are strong. Safflower has the effect of activating blood circulation, dispersing blood stasis, and relieving pain. A natural pigment named safflower yellow (SY) can be extracted from safflower petals. Chemically, SY is a water-soluble flavonoid and the main active ingredient of safflower. The main chemical constituents, pharmacological properties, and clinical applications of SY are reviewed in this paper, thereby providing a reference for the use of safflower in preventing and treating human diseases. Methods . The literature published in recent years was reviewed, and the main chemical components of SY were identified based on chemical formula and structure. The pharmacological properties of hydroxysafflor yellow A (HSYA), SYA, SYB, and anhydrosafflor yellow B (AHSYB) were reviewed. Results . The main chemical constituents of SY included HSYA, SYA, SYB, and AHSYB. These ingredients have a wide range of pharmacological activities. SY has protective effects on the heart, kidneys, liver, nerves, lungs, and brain. Moreover, its effects include, but are not limited to, improving cardiovascular and cerebrovascular diseases, abirritation, regulating lipids, and treating cancer and diabetic complications. HSYA is widely recognised as an effective ingredient to treat cardiovascular and cerebrovascular diseases. Conclusion . SY has a wide range of pharmacological activities, among which improving cardiovascular and cerebrovascular diseases are the most significant.